Development of a quantum dot-encoded microsphere suspension assay for the genotyping of single nucleotide polymorphisms - Thiollet, Sarah (Cranfield University, 2009)
This thesis describes the investigation of quantum dot-doped particle fluorescent technology commercially available for its application to analyte profiling in suspension. The first part of the thesis described the characterisation of the quantum dot-encoded microspheres, QDEMs, developed by Crystalplex (PA, USA). The multiple fluorescence signatures of QDEMs were analysed using microscopy and flow cytometry technology which provided high-content measurements with a single excitation sources and multiple emission wavelength detectors. The sensitivity and stability of the materials was evaluated under typical biomedical conditions encounter in multiple analyte suspension assays. Novel analytical parameters were defined to study QDEM stability and confocal microscopy detection system was used to provide structural and fluorescent imagines of the fluorescent microspheres under various conditions. Composition of the aqueous environment, temperature and physical forces applied to QDEM induced changes in their fluorescent codes and structural properties. Optimal conditions were then defined for the application of the material to biomedical assays. In a second stage, a conjugation method was developed to produce optimised QDEM bioconjugates for the detection of single strand DNA in suspension. The impact of the conjugation buffer, the concentration and the structure of oligonucleotides was evaluated to optimise QDEM bioconjugates. Then, a novel approach was investigated to optimise the hybridisation of ssDNA to QDEM bioconjugates. Experimental design with response surface methodology determined optimum conditions for the hybridisation of oligonucleotides to QDEM surface in suspension array. Finally, the specific hybridisation of ssDNA to QDEM bioconjugates in a small liquid format adapted to single nucleotide polymorphism detection was demonstrated. The work presented here shows the potential of QDEM bioconjugates for suspension array technology and DNA genotyping. Further, this report highlights the challenges that remain for QDEM fluorescent technology to be reliable for biomedical and suspension array applications.